Shared decision-making and behaviour change collide: an analysis of consultations discussing clinical trial recruitment - Stephen, Abigail; Matuluko, Ayodeji; Carroll, Kelly; Coffey, Taylor; Lawrie, Louisa; Sherratt, Frances; Hudek, Natasha; Lorencatto, Fabianna; Presseau, Justin; Marlin, Susan; Richards, Dawn P.; Brehaut, Jamie; et al. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Recruitment to clinical trials is often challenging, and evidence on effective recruitment strategies remains limited. Framing trial recruitment as a behaviour, amenable to change, enables the application of behavioural science frameworks to better understand and potentially improve recruitment processes. Since trial participation is also a preference-sensitive decision, shared decision-making (SDM) may further enhance ethical recruitment. The present study aimed to explore how behavioural taxonomies and SDM frameworks can be applied to recruitment consultations to identify behaviour change techniques (BCTs) and assess the extent of SDM. Methods A secondary analysis was conducted on 53 audio-recorded consultations; consultations from 3 trials in oncology and gastroenterology were sampled. The action, actor, context, target, and time (AACTT) framework was used to define recruitment behaviours, which were then coded using the Behaviour Change Technique Taxonomy v1 (BCTTv1). SDM was assessed using the 5-item ‘Observing Patient Involvement’ (OPTION5) tool, which evaluates patient involvement in decision-making. Descriptive statistics and frequency counts were used to analyse the data. Results Twenty-one of the 93 BCTs in the BCTTv1 were identified across all consultations. The most frequently coded BCTs were 5.1 (information about health consequences) and 5.3 (information about social and environmental consequences), both present in all consultations. No substantial difference in the total number of BCTs was observed between trial consenters (M = 6.8, SD = 1.5) and decliners (M = 6.4, SD = 2.1). However, some techniques showed variability: BCT 7.1 (prompts and cues) appeared more frequently in consultations with consenters (84%) than decliners (38%), while BCT 1.4 (action planning) was more frequent in decliners (44%) than consenters (27%). SDM, as measured by OPTION5, was low overall, with a mean score of 27.7 (SD = 12.2) out of 100, with no significant differences across trials or participant groups. Conclusions This study demonstrates the feasibility of applying behavioural science and SDM frameworks to analyse trial recruitment consultations. While a range of BCTs were identified, SDM efforts were generally low. Recruitment practices may benefit from more deliberate consideration of these techniques and greater emphasis on shared decision-making to support informed choices.